The Effect of Macroeconomic Uncertainty on Firm Decisions - Saten Kumar; Yuriy Gorodnichenko; Olivier Coibion (Institute of Labor Economics (IZA), 2022)
Using a new survey of firms in New Zealand, we document how exogenous variation in the macroeconomic uncertainty perceived by firms affects their economic decisions. We use randomized information treatments that provide different types of information about the first and/or second moments of future economic growth to generate exogenous changes in the perceived macroeconomic uncertainty of some firms. The effects on their decisions relative to their initial plans as well as relative to an untreated control group are measured in a follow-up survey six months later. We find that as firms become more uncertain, they reduce their prices, employment, and investment, their sales decline, and they become less likely to invest in new technologies or open new facilities. These ex-post effects of uncertainty are similar to how firms say they would respond to higher uncertainty when asked hypothetical questions.
Keywords: E3; E4; E5; 330; uncertainty; firm decisions; surveys; randomized control trial